A comunicação nos fluxos criativos como agir de sobrevivência, no Centro Livre de Artes Cênicas (CLAC) - Prado, Rosemeire Alcantara (2019)
Technological systems, characterized by the logic of body apps and online living (KATZ, 2014), reproduce behaviors and abilities of these environments in offline life, as well as productivity demands, competitiveness and self-entrepreneurship abilities (DARDOT and LAVAL, 2016). To produce alternatives to these configurations is an urgent attitude, as these new cognitive habits redraw the notions of alterity, empathy and shared acting, evolutionarily operations that are necessary to survival maintenance according to social neuroscientist John T. Cacioppo and his co-editor William Patrick (2010), main references in this dissertation, for their investigations about loneliness and social connection. This research starts from the hypothesis that creative flows of the dancing body on the knowledge production of one's sensorimotor experiences, potentialized by the investigation of connection perspectives proposed here and defined as image (DAMÁSIO, 2018, 2000), form and concept (LAKOFF and JOHNSON, 1999) are important communication operations of survival. This notion of survival develops by constant exchanges in networks of codependent social connections, and not only by preserving the life of the individual. The empirical object was a clipping of the discipline “Creation processes in dance and interdisciplinary dialogues”, taught at Centro Livre de Artes Cênicas (CLAC), in São Bernardo do Campo (SP), for two classes, in 2015 and 2016, respectively. This public dance and theater project was held from December 2011 to December 2016. Reflections and discussions, formulated on the experiments produced by these classes during the lessons, based on connection perspectives (as well as it's explanation) along with the references cited, have defined the investigation methodology of this research. The objective was to raise reflections upon the problem presented and around the alternatives amidst communication potentialities and creative flows exchanges. The Bodymedia Theory (KATZ and GREINER, 2005) is the basis for understanding body and communication, applied both in classes held at CLAC, and in this research